Pengaruh Ukuran Perusahaan Profitabilitas dan Win/Lose Stock Terhadap Income Smoothing Pada Perusahaan Jasa Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2018: Keywords: Company Size; Profitability; Income Smoothing - Rona Pramitasari Siswanto Putri (Universitas Negeri Surabaya, 2022)
This study aims to determine the effect of company size, profitability, win / lose stock on income smoothing actions in service companies which listed on the IDX during 2015-2018. In this study using quantitative methods and data sourced from company annual reports with logistic regression analysis techniques. The results of the research in the form of variable firm size, profitability, and win / lose stock have no effect on income smoothing or income smoothing.